The efficacy of low-level laser therapy in alleviating genitourinary syndrome of menopause and stress urinary incontinence: the pilot study - Wu, Pei-Chi; Lin, Ho-Hsiung; Chen, Chi-Hau; Kuo, Yih-Shing (Frontiers in Medicine, 2025)
ObjectiveGenitourinary syndrome of menopause (GSM) and stress urinary incontinence (SUI) are prevalent among women. While low-level laser therapy (LLLT) has been employed for wound healing, no studies have explored its effectiveness in treating GSM and SUI.MethodsBetween September 2022 and August 2023, all women received LLLT for GSM and SUI at the gynecologic outpatient clinic of a hospital were retrospectively reviewed. The treatment was administered once a week for 8 weeks. Vaginal Health Index (VHI) and pre- and post-treatment questionnaires were utilized to assess lower urinary tract symptoms (LUTS).ResultsA total of 41 women were enrolled, including 24 (59%) with SUI and 22 (52%) with GSM (5 women reported both conditions). Significant improvements were observed in all VHI items for both groups. Total scores for ICIQ-SF (International Consultation on Incontinence Questionnaire-Short Form), UDI-6 (Urogenital Distress Inventory-6), IIQ-7(Incontinence Impact Questionnaire-7), USS (Urgency Severity Scale), and OABSS (Overactive Bladder Symptom Score) demonstrated significant enhancements in all women and specifically in the GSM group. In the SUI group, USS and OABSS significantly improved, with more domains in KHQ (King’s Health Questionnaire) showing improvement compared to the GSM group. In the GSM group, lubrication, pain, and the total score of FSFI (Female Sexual Function Index) improved significantly, while no significant enhancement in sexual function was observed in the SUI group.ConclusionThis pilot study indicates that LLLT is a safe, cost-effective, and straightforward treatment for alleviating GSM and SUI symptoms. Women with GSM experienced improvements in LUTS and sexual function, while women with SUI demonstrated improvements in urinary urgency and LUTS-related quality of life. This study represents the first application of LLLT in gynecology.